2010
DOI: 10.1038/tpj.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 polymorphism in patients with eating disorders

Abstract: CYP2D6 polymorphism is associated with variability in drug response, endogenous metabolism (that is, serotonin), personality, neurocognition and psychopathology. The relationship between CYP2D6 genetic polymorphism and the risk of eating disorders (ED) was analyzed in 267 patients with ED and in 285 controls. A difference in the CYP2D6 active allele distribution was found between these groups. Women carrying more than two active genes (ultrarapid metabolizers) (7.5 vs 4.6%) or two (67 vs 58.9%) active genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Originally, an incidental observation in forensic studies aimed at evaluating the effect of poor metabolism on fatal intoxication; 151,152 this finding was replicated in two independent studies explicitly designed to test the association 153,154 and in further three independent databases of patients in treatment for depression 155,156 and eating disorders. 157 In the recent studies, the association is driven by a higher incidence and severity of suicidal behavior in the UM group. 155,156 Of possible significance to this association are data suggesting increased frequency of the CYP2D6 UM phenotype in depression more generally.…”
Section: Individual Differences In Behavior and Psychiatric Disordersmentioning
confidence: 98%
“…Originally, an incidental observation in forensic studies aimed at evaluating the effect of poor metabolism on fatal intoxication; 151,152 this finding was replicated in two independent studies explicitly designed to test the association 153,154 and in further three independent databases of patients in treatment for depression 155,156 and eating disorders. 157 In the recent studies, the association is driven by a higher incidence and severity of suicidal behavior in the UM group. 155,156 Of possible significance to this association are data suggesting increased frequency of the CYP2D6 UM phenotype in depression more generally.…”
Section: Individual Differences In Behavior and Psychiatric Disordersmentioning
confidence: 98%
“…A high frequency of Ultra-rapid Metabolizers (UMs) has been previously described in Spanish population Peñas-Lledó et al, 2012). Given the Iberian Peninsula's influence on the hybrid population, we hypothesized that a high frequency of UMs would be present in the mestizo population.…”
mentioning
confidence: 99%
“…CYP2D6 has many polymorphisms associated with personality traits and neurologic or psychiatric disorders. A previous study showed that female CYP2D6 ultra-rapid metabolizers were more frequent among patients with eating disorders due to the alteration of brain serotonin concentration (Peñas-Lledó et al, 2012). This study indicated that enzymes capable of catalyzing the generation and elimination of endogenous compounds possibly regulate the local concentration and function of the endogenous compounds in the brain.…”
Section: Downloaded Frommentioning
confidence: 70%